FROM ANIMATION TO REALITY: Race/Gender, the Myth of the American Dream and Tom and Jerry Cartoons - Aravind , Aju (Journal of Dharma, 2016)
The animated cartoon Tom and Jerry (T&J) is widely acclaimed as perhaps one of the most ‘innocent’ and ‘pure’ forms of entertainment. But they also infuse in the viewers a perception which underlines the concept of ‘preferred reading,’ to propagate the ideologies of ‘producers and transmitters of the text’ which was essentially racial and gendered. This paper examines the animated cartoon T&J as a cultural-political and historical phenomenon and analyzes how they manipulate identities and images of the black female to construct a potent ideology that sustains the material and cultural interests of its creators.